2020
DOI: 10.1016/j.eplepsyres.2019.106252
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for epilepsy surgery referrals in Bhutan: A cohort study

Abstract: Objective-To quantify the missed opportunities for epilepsy surgery referral and operationalize the Canadian Appropriateness of Epilepsy Surgery (CASES) tool for use in a lower income country without neurologists.Methods-People with epilepsy were recruited from the Jigme Dorji Wangchuck National Referral Hospital from 2014-2016. Each participant was clinically evaluated, underwent at least one standard EEG, and was invited to undergo a free 1.5 Tesla brain MRI. Clinical variables required for CASES were operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While the utilization of epilepsy surgery seems to be on an upward trend in these three countries, it is important to note the gross under‐representation of other LMICs particularly in Africa. Strategies to address these inequities should focus not only on supporting investments in infrastructure and expertise, but also ensure better referral 27,34 and promote judicious utilization of resources 35 …”
Section: Discussionmentioning
confidence: 99%
“…While the utilization of epilepsy surgery seems to be on an upward trend in these three countries, it is important to note the gross under‐representation of other LMICs particularly in Africa. Strategies to address these inequities should focus not only on supporting investments in infrastructure and expertise, but also ensure better referral 27,34 and promote judicious utilization of resources 35 …”
Section: Discussionmentioning
confidence: 99%
“…A recent survey for Africa [11] found that epilepsy surgery is performed in only 8 out of 51 countries, with only one country reporting invasive presurgical diagnostics. As a consequence, clear-cut cases with excellent outcome prognosis, such as patients with mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis (HS), accumulate in LMIC [12][13][14], even though the establishment of low-cost epilepsy surgery programs is feasible in countries with resource-poor settings [15,16]. Furthermore, with a rapidly growing population in LMIC, the gap between the number of patients who could benefit from surgical intervention and those who can actually receive it is widening yearly [11], making the initiation of surgical epilepsy services for those countries a timely issue.…”
Section: Introductionmentioning
confidence: 99%